Reimagining teacher professional development in the age of AI: Indonesian EFL teachers’ beliefs and pedagogical adaptations in writing classrooms - Nur Halimah; Afif Ikhwanul Muslimin; Denchai Prabjandee (Journal of Research on English and Language Learning (J-REaLL), 2026)
Although artificial intelligence has gained growing attention in language education, previous research has largely emphasized technical effectiveness and student outcomes, while teachers’ professional experiences remain insufficiently examined. This study explores how Indonesian EFL lecturers perceive the use of artificial intelligence in academic writing instruction, how they adjust their pedagogical practices, and how these experiences shape their professional development and professional identity, particularly in writing assessment. Employing a phenomenological approach, data were collected through semi-structured interviews, classroom observations, and teaching documents involving twelve lecturers from East Java and Central Indonesian regions. The findings reveal interconnected experiences influenced by institutional readiness, access to digital infrastructure, and lecturers’ pedagogical beliefs. Participants reported a shift in professional identity from primary evaluators of student writing toward facilitators who guide learners in critically engaging with artificial intelligence-generated feedback. In the absence of systematic institutional training, lecturers relied heavily on informal peer communities as spaces for learning, reflection, and sharing instructional strategies. The study suggests that professional development for artificial intelligence-supported writing instruction should move beyond technical orientation and provide sustained, context-sensitive support that integrates ethical awareness, reflective practice, and collaborative learning. While the qualitative design and limited number of participants require cautious interpretation, the findings contribute to broader discussions on teacher professional development in technologically evolving educational contexts.